2012
DOI: 10.5152/akd.2012.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levosimendan and dobutamine treatment on QT dispersion in patients with decompensated heart failure: a prospective study

Abstract: Objective: We investigated the effect of intravenous levosimendan on QT dispersion compared with intravenous dobutamine in patients with acute decompensated heart failure. Methods: This prospective cohort study included 38 patients who were admitted with acute decompensated heart failure (New York Heart Association functional class III-IV). Twenty-five patients (11 men, 14 women; mean age 70.5±11.13 years) were treated with levosimendan infusion and 13 patients (5 men, 8 women; mean age 71.08±6.86 years) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Because; the QT and Tp-e parameters did not significantly change with levosimendan infusion in the inotropic and without inotropic treatment group. Paksoy et al [16] investigated the effect of intravenous levosimendan and dobutamine on QT parameters and found that levosimendan and dobutamine did not have a significant effect on QT parameters (16). In our study group we used dopamine/dobutamine and levosimendan concomitant at inotropic therapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because; the QT and Tp-e parameters did not significantly change with levosimendan infusion in the inotropic and without inotropic treatment group. Paksoy et al [16] investigated the effect of intravenous levosimendan and dobutamine on QT parameters and found that levosimendan and dobutamine did not have a significant effect on QT parameters (16). In our study group we used dopamine/dobutamine and levosimendan concomitant at inotropic therapy.…”
Section: Discussionmentioning
confidence: 97%
“…In our study group we used dopamine/dobutamine and levosimendan concomitant at inotropic therapy. However, Paksoy et al [16] prolongation is usually associated with cardiac ischemia. QT is not affected by inotropic therapy unless patients have cardiac ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, probably keeping electrolyte balance within normal limits prevented the development of lethal arrhythmias. In our recently published study, therapeutic doses of levosimendan did not have a significant effect on QT parameters the predictors of arrhythmias, in patients with decompensated HF when compared with dobutamine infusion (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Increased QTc and/or QTd are known to be the cause of ventricular arrhythmia in various systemic diseases and lead to an increase in mortality and morbidity. Increased QTd has been shown to be an important prognostic factor in several cardiovascular conditions such as coronary artery disease, congestive heart failure and cardiomyopathy (21,32). Literature reviews found the QTd to vary mostly between 30 and 60 msec in normal subjects, although average values around 70 msec were also reported (33).…”
Section: Comparison Of Pd Qtd and Hr Values Between Gs And Control Gmentioning
confidence: 99%
“…Measurements were not taken in derivations if the end of T wave was not determined or the amplitude was low. QTd is defined as the difference between QTmax and QTmin (21). The intervals of QT were corrected according to heart rate (HR) using the Bazett formula "Corrected QT interval (QTc)=QT/ √R-R" and expressed as QTc.…”
Section: Diagnosis Of Gsmentioning
confidence: 99%